Performance of international securities markets - Heiko Schmiedel (Bank of Finland, 2004)
This study evaluates the performance of international securities markets by analysing the efficiency, economies of scale, and technological development in stock exchanges and securities settlement systems.Implications for future policy and market design are also addressed.This work provides empirical support for theoretical projections in research on stock markets.At the heart of this study is an international comparison that explores productivity, efficiency, and innovation of a wide range of stock exchanges over recent years.There is evidence of considerable variability in the efficiency of stock exchanges, both within Europe and world-wide.The evidence also indicates a positive relationship between the organisational structure and performance of the stock exchanges.It also reveals that technological change is the key driver of rising total productivity and appears to be advantageous for the performance of international securities markets.Furthermore, the study conveys how strategic interactions between stock exchanges are affected by network activity, and examines its influence on stock market performance.The adoption of network strategies was observed to be a promising tool for creating added value in the provision of trading services, and appears to be a crucial component in the strategic decision-making and performance of stock exchanges.The study also examines how far consolidation of and mergers among securities depository and settlement systems might go in the face of economies of scale and technological advancements.The results indicate substantial scale economies in settlement activities, although the extent of such effects differs by size of settlement institution and region. Overall, cost effectiveness has improved in recent years, partly due to innovations and upgrades in settlement technologies. Finally, the results are relevant for practitioners, policymakers, monetary and regulatory authorities, as they suggest further equity market integration.Networks, alliances, mergers and so forth seek to improve market efficiency, explore the benefits of economies of scale, and reduce the average transaction cost to end-users.
URN:NBN:fi:bof-201408071708
Keywords: C2; F3; G2; L2; O3; 330; exchanges; settlement systems; networks; economies of scale; efficiency